Entrepreneurial performance in accordance with the competitive intelligence and strategic - داود, فضيلة سلمان (Journal of Economics and Administrative Sciences, 2016)
The research aims to study the entrepreneurial performance of the banks, according to the intelligence of competitive and strategic as the entrepreneurial performance is the one who does not stand the benefits of excellence in accomplished when just achieving the bank's objectives planned, but exceed it down to creativity in accomplishing these goals in a manner leads to making a entrepreneurial bank in the markets and the focus the eyes of competitors and the banks and other Following his example.Was chosen the subject of research and strategic intelligence and competitive because of its impact on the strategic success of the banking sector, the fact is the entrepreneurial in the Iraqi banking market private banking sector, These two variables have the impact on the outstanding performance and who will we measure qualitative sample of private banks in the city of Baghdad, has been selected sample (59 people from the department managers and the Division unit) for four community banks, namely, (the Middle East, the National Investment Bank, Bank of Kurdistan, and the National Bank for Investment), and through statistical analysis and extraction of the results found that there is a very strong correlation and the impact of intelligent competitive and strategic in the banking performance, as noted there is the influence of the dimensions of competitive intelligence and strategic dimensions in the performance of the entrepreneurial banks of the research sample..